PSVIII-27 Interactions between the stage of maturity of Eragrostis tef hay and supplemental energy source on forage utilization in beef heifers. (30th November 2020) - Stevens, Allison; Myers, Cheyanne; Hall, John B; Chibisa, Gwinyai E
Abstract: This study evaluated the interaction between the stage of maturity of Eragrostis tef (teff) grass and supplemental energy source on ruminal fermentation characteristics and nitrogen (N) utilization. Six ruminally-fistulated beef heifers were used in a 3 × 3 split-plot design (21 d periods). The whole plot factor was stage of maturity of teff hay [early- (EH) or late-heading (LH)], and the subplot factor was supplemental energy source [no supplement (CON), rolled corn grain or beet pulp pellet (BP)] fed at 0.5% of body weight. Feed intake was measured daily. Indwelling pH loggers were used to measure ruminal pH (d 14 to 21) and ruminal fluid was collected from d 19 to 21 to determine fermentation characteristics, as were feces and urine to measure N excretion. Data was analyzed using PROC MIXED in SAS. There was no stage of maturity × supplement interaction for all measurements (P ≥ 0.17). Although dry matter intake (DMI) tended to be greater (P = 0.07) for heifers fed EH than LH hay, it did not differ (P = 0.88) across supplements. Ruminal acetate concentration tended (P = 0.098) to be greater for EH than LH heifers, whereas butyrate, isobutyrate, and isovalerate concentrations were greater (P ≤ 0.045) for BPP than CON heifers. However, the duration and area pH < 6.2 and 5.8 did not differ (P > 0.12) across treatments. Except for microbial N flow, which was greater (P < 0.01) for EH than LH heifers, there was no stage of maturity or supplement effect (P ≥ 0.14) on measures of N utilization. In summary, feeding teff hay harvested at the EH than LH stage of maturity increased DMI and microbial N supply, whereas feeding corn and BP as energy supplements to beef heifers had no effect on ruminal pH.